Effects of different anticoagulant drugs on the prevention of complications in patients after arthroplasty: A network meta-analysis. Issue 40 (October 2017) - Gao, Ji-Hai; Chu, Xiu-Cheng; Wang, Lin-Liang; Ning, Bo; Zhao, Chuan-Xin
Abstract: Background: After arthroplasty treatment, some complications commonly occur, such as early revision, infection/dislocation, and venous thromboembolism (VTE). This study aims to use a network meta-analysis to compare effects of 9 anticoagulant drugs (edoxaban, dabigatan, apixaban, rivaroxaban, warfarin, heparin, bemiparin, ximelagatran, and enoxaparin) in preventing postoperative complications in arthroplasty patients. Methods: After retrieving PubMed, Embase, and Cochrane Library database from the inception to November 2016, randomized controlled trials were enrolled. The integration of direct and indirect evidences was performed to calculate odd ratios and the surface under the cumulative ranking curves. Nineteen eligible randomized controlled trials were included. Results: The network meta-analysis results showed that compared with warfarin, edoxaban, apixaban, and rivaroxaban had a lower incidence rate in asymptomatic deep venous thrombosis, which indicated that edoxaban, apixaban, and rivaroxaban had better effects on prevention. Similarly, in comparison to enoxaparin, edoxaban and rivaroxaban had better effect; rivaroxaban was better than ximelagatran in preventive effects. Compared with apixaban, edoxaban, dabigatan, rivaroxaban, and enoxaparin had a higher incidence rate in clinically relevant non-major bleeding, which showed that preventive effects were relatively poor. In addition, the results of the surface under the cumulative ranking curves showed that rivaroxaban and bemiparin worked best on symptomatic deep venous thrombosis and pulmonary embolism. In terms of bleeding, apixaban and warfarin had better preventive effects. Conclusion: Our findings suggested that rivaroxaban may work better in terms of symptomatic deep venous thrombosis and pulmonary embolism, whereas apixaban had better preventive effects in bleeding. Abstract : Supplemental Digital Content is available in the text